PENANAMAN NILAI KARAKTER GEMAR MEMBACA BERBASIS PEMBIASAAN DAN KETELADANAN TERHADAP KEMAMPUAN BERBAHASA SISWA SEKOLAH DASAR - Efi Ika Febriandari (STAI Ma'had Aly Al-Hikam Malang, 2019)
Advantage the article has the purpose of describing how to instill reading like the charater of an avid reader and habituation which have impact on children's language skills.Â Based on the literature reviews show that the elementary school children's reading interest is very low. It is influenced by the lack of awareness in reading importance of reading and external support such as the direction and guidance of parents and teachers, the availability of reading material, and the attractiveness of available books. For this reason, there is something that it takes for habituation and exemplary efforts that are made both from the awareness of oneself, family, teachers and the surrounding environment so that children are accustomed to reading books and make children to enjoy reading books which in turn can increase language skills in children. Habitual and exemplary methods are effective ways to instill the character of reading fondness. The more someone likes to read, the more knowledge is gained. To inculcate the reading fondness character values, it takes habituation and example to realize the culture of fond reading. The fond reading character is a form of language skills development. The more skilled a person in language, the more brilliant, and clearer the way he/she thinks because their processes reading there is a process of critical thinking.